Evaluation on different forms of Moringa Oleifera seeds dosing on sewage sludge conditioning - Kien, Tat Wai; Idris, Azni; Megat Johari, Megat Mohd Noor; Mohammad, Thamer A.; Ghazali, Abdul Halim; Muyibi, Suleyman Aremu (Desalination Publications, 2009)
The effect of different form of dosing using Moringa oleifera seeds in sewage sludge conditioning was studied. Settled activated sludge after clarification process was obtained from sludge holding tank in Sewage Treatment Plant, Taman Tun Dr. Ismail, Kuala Lumpur, Malaysia. In this study, sludge conditioning with Moringa oleifera seeds in 3 different forms: dry powder, distilled water extracted and salt extracted (1 N NaCl) — were studied in comparison with chemical polymer, Zetag 7653. The study applied operator’s specification, Indah Water Konsortium Sdn. Bhd., Malaysia (IWK) with preparation of Moringa oleifera in water and salt stock solution and Zetag 7653 stock solution were done at 650 rpm for 1 h. Sludge conditioning was then operated at 60 rpm for 45 min using jar test apparatus. Using specific resistance to filtration (SRF) as a parameter, Moringa oleifera in dry powder form at dosage of 2000 mg/L was comparable to 50 mg/L Zetag 7653 in reducing the value from 8.0×1010 to 3.3×1010 m/kg (2.5 times of magnitude). Therefore, Moringa oleifera in dry powder form was as effective as Zetag 7653. There was no significant change in CST between the three methods of extraction for Moringa oleifera. Without applying filtration using muslin cloth, sludge solid content when dosed with Moringa oleifera in distilled water extracted form showed the least increment at 17.08%.